Accounting Education Challenges in Technology Driven Auditing Environments (gjstudies, 2016)
The rapid integration of sophisticated technologies into auditing practices, includingdata analytics, artificial intelligence, and continuous monitoring systems, has precipitated a significant misalignment between traditional accounting education curriculaand the competencies required in modern audit engagements. This research investigates the specific pedagogical challenges arising from this technological shift, movingbeyond generic calls for curriculum updates to identify the core epistemological andskill-based disconnects. The study employs a novel, tripartite methodological framework combining a longitudinal analysis of auditing job descriptions (2000-2005), a qualitative discourse analysis of pedagogical materials from leading accounting programs,and a series of simulated audit case studies administered to both students and practitioners. Our findings reveal a persistent ’automation paradox’ in education, whereinstruction focuses on manual procedures that software now performs, while underdeveloping the critical evaluation, interpretive, and ethical reasoning skills needed tooversee automated systems. We identify a critical gap in teaching ’technological skepticism’—the ability to interrogate the assumptions, algorithms, and data integrity withinaudit technologies. Furthermore, the results demonstrate that current educationalmodels inadequately prepare students for the collaborative, interdisciplinary nature oftechnology-driven audits, which require integration with IT specialists and data scientists. The paper concludes by proposing a foundational restructuring of accountingpedagogy centered on ’Audit Technology Literacy,’ a framework that embeds understanding of technological capabilities and limitations within core audit concepts ratherthan treating technology as a separate subject. This represents a significant departurefrom existing educational approaches and offers a concrete pathway for bridging thegrowing divide between academic preparation and professional practice in the auditingdomain.